A hybrid ranking ELECTRE algorithm and its applications in agricultural decision-making. (21st January 2020) - Simić, Dragan; Gajić, Jovana; Ilin, Vladimir; Simić, Svetislav D; Simić, Svetlana
Abstract: A vast number of real-world problems can be associated with multi-criteria decision-making (MCDM). This paper discusses MCDM in agricultural industry. Methodological hybrid analytical hierarchy processes, ELECTRE I and genetic algorithm method are proposed here, and it is shown how such a model can be used for complete ranking model. The proposed hybrid bio-inspired method is implemented on real-world data set collected from agricultural industry in Serbia.